2014
DOI: 10.1603/me13088
|View full text |Cite
|
Sign up to set email alerts
|

Description of Third Instars of <I>Cochliomyia minima</I> (Diptera: Calliphoridae) From West Indies, and Updated Identification Key

Abstract: The blow fly Cochliomyia minima Shannon is endemic to the Caribbean, and it has great potential for forensic applications because of its abundance and broad distribution in the region. However, its larval stages are unknown. Here, I update previously published identification keys by describing for the first time the morphology of C. minima larvae. The larvae of C. minima are found to be very similar to those of Cochliomyia macellaria F., but the former can be easily identified by the oral sclerite completely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In recent studies of Cochliomyia minima in Puerto Rico, Yusseff-Vanegas (2014) reported that Cochliomyia minima prefer highly humid areas and can tolerate relatively cool conditions at altitudes >800m, while this species is absent from extremely dry and hot areas. Similar results were found in Dominican Republic and Cuba where Cochliomyia minima was found abundantly in tropical and subtropical rain/moist forest even at altitudes >1300m, but absent from dry forest (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies of Cochliomyia minima in Puerto Rico, Yusseff-Vanegas (2014) reported that Cochliomyia minima prefer highly humid areas and can tolerate relatively cool conditions at altitudes >800m, while this species is absent from extremely dry and hot areas. Similar results were found in Dominican Republic and Cuba where Cochliomyia minima was found abundantly in tropical and subtropical rain/moist forest even at altitudes >1300m, but absent from dry forest (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, due to their abundance and broad distribution in this region, including Cuba, Dominican Republic, Jamaica, Puerto Rico, Virgin Islands, Bahamas and Cayman Islands (Hall 1948, Dear 1985, Whitworth 2010) they have an enormous forensic potential. For example, recent studies conducted in Puerto Rico showed that Cochliomyia minima is abundant and widely distributed on the island, and that adults are attracted to, and feed on, carrion (Yusseff-Vanegas 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preservation of a portion of the specimens was accomplished by hot water kill and placement in 70% ethanol [12,17] and the remainder of the specimens were reared to confirm identification. Identification of the larvae was accomplished with the use of taxon and life stage appropriate keys (e.g., [18,19,20,21,22]).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we show DNA barcoding to be useful in overcoming these problems and provide tools to accelerate the identification and discovery of species. This is particularly important in areas like the Caribbean, where studies of insects involved in cadaveric decomposition are scarce (Whitworth, 2010;Yusseff-Vanegas & Agnarsson, 2016;Yusseff-Vanegas, 2007;Yusseff-Vanegas, 2014). One of the first steps required for this approach is creating a reliable DNA barcode database that can be used with confidence in order to identify unknown specimens found in death scenes investigation (DeBry et al, 2013;Harvey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%